Manajemen Pelayanan dalam Peningkatan Mutu Pendidikan Inklusi Sekolah di Tulungagung - Januariani; Prim Masrokan; Imam Fuadi (STAI Terpadu Yogyakarta, 2023)
This study aims to determine the implementation of service management in improving the quality of inclusive education. This research was conducted at SD Muhammadiyah 1 Tulungagung, SDI Al-Azhaar Tulungagung, and MI Modern SAKTI Tulungagung. This research uses a qualitative approach of the type of case study. The results showed that the management of inclusion education services was carried out by providing facilities and infrastructure in accordance with the needs of Students with Special Needs (PDBK), competent educators, modifying the curriculum and assessment system for PDBK, and creating a pleasant learning atmosphere. The implementation of service management in the three educational institutions has their own characteristics in accordance with the vision and mission of the school. Although there are different objectives, basically the objectives of education still refer to the quality standards specified in the applicable laws and regulations.